1984
DOI: 10.1039/an9840901025
|View full text |Cite
|
Sign up to set email alerts
|

Fibre-optic pH probe based on the use of an immobilised colorimetric indicator

Abstract: The construction of a pH sensor, having the configuration of a probe, is described. The probe utilises a plastic-fibre bundle at the end of which is fabricated a sensitive tip consisting of a styrenedivinylbenzene copolymer supporting an adsorbed colorimetric pH indicator, which is retained in position by a membrane of polytetrafluoroethylene (PTFE). Changes in pH in the vicinity of the sensitive tip cause a variation in the attenuation of specific reflected visible radiation bands. Initial results and perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…The decreased quantum yield has a minor effect on the pH sensitive fluorophore due to the short decay time but due to the longer lifetime of the pH insensitive dye, a larger effect is seen when integrating the t ex time window. The observed temperature dependence of the pH spot is similar to that reported for an immobilised sensor spot by Schroeder et al [53], but smaller than reported by Kirkbright et al [77]. The temperature dependence requires the accurate recording of temperature and a correction of the final pH readings.…”
Section: Temperature Dependencesupporting
confidence: 59%
“…The decreased quantum yield has a minor effect on the pH sensitive fluorophore due to the short decay time but due to the longer lifetime of the pH insensitive dye, a larger effect is seen when integrating the t ex time window. The observed temperature dependence of the pH spot is similar to that reported for an immobilised sensor spot by Schroeder et al [53], but smaller than reported by Kirkbright et al [77]. The temperature dependence requires the accurate recording of temperature and a correction of the final pH readings.…”
Section: Temperature Dependencesupporting
confidence: 59%
“…Glass pH electrodes are unsuitable for certain applications like determination of intracellular pH, microscopy studies as well as measurement of extreme pH values (<1 or >9) [5]. New kinds of optical sensors have attracted great attention of researchers due to their possible applications in industrial, environmental, and medicinal areas [6,7]. Several kinds of optical pH and ion sensors have been published so far [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of immobilization techniques for pH indicating dyes have been used [9], including (a) dye entrapment in different materials such as cellulose acetate [10,11], sol-gel [12], PVC [7], methacrylic-acrylic copolymers [13] and different composites like SiO 2 /ZrO 2 -organic polymer (styrene/methyl methacrylate copolymer or Nafion) [14], (b) retention of dye by ion-exchange materials such as Amberlite XAD-2 resin [15] or Dowex l-X10 resin [16], in some instances including the ionexchanger containing dyes in polymeric encapsulated membranes using PVC [17], (c) adsorption of the dye on materials such as non-ionic styrene/divinylbenzene copolymer [18], polyester/lycra blends textile [19], cellulose [20], cellulose acetate [21], or polymer track membranes combining retention in surface and bulk [22], (d) covalent binding of dye by different synthetic strategies to form microparticles or membranes, in some cases formed on glass fibre, using different polymers such as polyacrylamide [8,23], triacetylcellulose [24], cellulose acetate [25,26], agarose [27] or polyamide [28], among others, (e) polymerization of monomers to prepare both membrane and dye, as with aniline [29] or pyrrole [30].…”
Section: Introductionmentioning
confidence: 99%